Emerging Destinations for New Generations of Swedish Students Studying Abroad (Comparative & International Education Series, 2021)
The number of students temporarily studying in another country to receive a post-secondary education has grown significantly since the 1970s. This study aims to learn more about what attracts Swedish outbound students when studying abroad. What are the popular study destinations? Can data reveal touristic preferences? Descriptive statistics from the Swedish Board of Student Finance are used, making it possible to scrutinize studying abroad on an aggregate level over a period of two decades. The results show that English-speaking countries are attractive to Swedish outbound students. Places growing in popularity are the countries of Poland, Japan, the Netherlands, South Korea, Singapore, and China, as well as the region of Hong Kong in particular. However, more than 50 percent of outbound students study in Europe. In these troubling and uncertain times we are living in, with Covid-19 and other crises hampering worldwide travel, it is difficult to predict the long-term effects on mobility.